Revisiting Local Governance Discourse: Theoretical Foundations and Legal Trajectory in Nepal - Shahi, Min Bahadur; Kharel, Suman (Molung Educational Frontier, 2026)
This paper addresses the central research question: to what extent do local government theories contemplate the fundamental essence of local governance and its accountability? Drawing on an extensive review of secondary literature, including books, academic journals, and policy documents, the study explores key theories, including governance theory, deliberative democracy, public choice theory, and accountability approaches. The analysis is thematically structured, beginning with conceptual clarifications and progressing toward theoretical and policy-oriented insights. The findings reveal that the philosophical foundation of local government is rooted in liberal democratic values, public choice theory, and the principles of decentralization. The paper highlights that decentralized governance systems require proximity-based engagement between service providers and citizens, with social accountability serving as a key mechanism. In Nepal, the trajectory of local governance reflects a gradual shift from centralized control toward a more participatory and decentralized model, marked by legislative and constitutional milestones, including the Local Government Operational Act 2017 and the 2015 Constitution. Overall, the study offers a comprehensive synthesis of the theoretical underpinnings and conceptual frameworks surrounding local government and its accountability. It emphasizes the evolving ideology of local governance, emphasizing responsiveness, ethics, effectiveness, and citizen-centric service delivery.